A missão como modelo de renovação da Igreja = The mission as a model for the renewal of the Church = La misión como modelo de renovación de la Iglesia - Silva, Roberto Marcelo Da (Teocomunicação, 2023)
Pope Francis proposed the mission as a model for the renewal of the Church. The Pontiff takes this invitation as a starting point and proposes to refl ect on the impact of the issue on some theological issues. The urgency of the mission must modify not only pastoral action, but also the theological language, because saying and doing are strongly linked. God, Jesus Christ, man, culture and the ethical consequences of missionary transformation are the themes addressed in this article. The article aims to verify perspectives concerning the mission of the Church, passing through a language or message that expresses divine mercy and that culminates in missionary ethical implications.